Studi Olah Gerak Lambung Kapal Pompong Nelayan Plastik High Density Polythylene - Siswandi. B, Muhammad Helmi (Techno Bahari, 2018)
Every object that floats in the water will have oscillation motion. This oscillation motion is defined as the motion of an alternating object around the equilibrium point with the same path and occurs periodically that is repeated over the same time span. Fishing vessel pompong that operate in the sea will encounter uncertain conditions caused by the force from the outside and the force from of the ship itself. In general, the fishing vessel of pompong in Bengkalis area made of from wood in this study are planning a ship model with a base material using high density polyethylene (HDPE) plastic with the main size of ship L = 8.8 m; B = 1.56 m; H = 1.05 m; and T = 06 m. The shape modeling of ship by using maxsurf then the evaluation of seakeeping by using seakeeper to find out the response of hull model to the wave of heave, roll, pitch movement and wave spectrum. Evaluation seakeeping of vessel conducted on two condition that is motionless condition and moving with speed 5 knot. On motionless condition the highest RAO of heave value is 1,362 at an angle of 900, the highest RAO of roll value of 6,674 at an angle of 900, the highest RAO of pitch value of 1.271 at the angle 00 and the wave spectrum at the angles 00, 450, 900 and 1350 have the same value with value of 0,488 rad/s. while at 5 knots the highest RAO of heave value is 1,283 at an angle of 900, the highest RAO of roll value of 6,668 at an angle of 900, the highest RAO of pitch value of 1,193 at an angle of 00 and the wave spectrum at an angle of 00 have the highest value reach out a value 4,61 rad/s.